Fractional-Order Active Disturbance Rejection Controller Design for Large Radio Telescope Antenna - Jian-Yu Jiang; Bin Wu; Ting Zhou (International Journal of Antennas and Propagation)
large radio telescope antennas are required in current astronomical research and deep space communication applications. The wind disturbance becomes a serious problem with an increase in the size of the antennas. Based on the typical antenna model, this work aims to design a fractional-order active disturbance rejection controller (FOADRC) for improving the accuracy of the antenna pointing mechanism in wind disturbance. First, the fractional-order active disturbance rejection control scheme is chosen to estimate and compensate both the wind disturbance and other uncertain mechanical dynamics. Afterwards, the relationship between the parameters of fractional-order extended state observer and the performance of disturbance suppression and noise immunity is revealed. The stability of fractional-order extended state observer is proved under similar assumptions as an integer order extended state observer. In addition, a stability region boundary calculation method is presented to simplify the parameter setting procedure. Finally, we perform simulations to verify the superiority of FOADRC in the antenna control system under wind disturbance. The results demonstrate that FOADRC has a good capability of resisting wind disturbance; at the same time, it limits the response overshoot and converges faster compared to other industrial controllers.